2005
DOI: 10.1269/jrr.46.111
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic Radiosensitivity of G0-Lymphocytes of Breast and Esophageal Cancer Patients as Determined by Micronucleus Assay

Abstract: Enhanced chromosomal radiosensitivity is a feature of many cancer predisposition conditions, indicative of the important role of chromosomal alterations in carcinogenesis. In this study the cytokinesis-blocked micronucleous assay was used to compare the radiosensitivity of blood lymphocytes obtained from Iranian breast or esophageal cancer patients (n = 50, n = 16; respectively) with that of control individuals (n = 40). For each sample, one thousand binucleate lymphocytes were analyzed before and after in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 33 publications
1
27
1
1
Order By: Relevance
“…34,35 We also reported a significant increase in radiation-induced DNA damage in breast cancer patients undergoing radiotherapy. 36 DNA damage in the form of telomere shortening has been linked to increased stress in a population of caregivers.…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…34,35 We also reported a significant increase in radiation-induced DNA damage in breast cancer patients undergoing radiotherapy. 36 DNA damage in the form of telomere shortening has been linked to increased stress in a population of caregivers.…”
mentioning
confidence: 73%
“…Radiation-induced DNA damage has been widely studied and reported by many, including our previous study. 36 In another work, Mozdarani et al 34 showed that there was an elevated spontaneous frequency of micronuclei in a breast cancer group compared to a control group. They also showed that breast cancer patients were 30% more sensitive to ionizing radiation than the age-and sex-matched control population.…”
Section: Integrative Cancer Therapies 6(3); 2007mentioning
confidence: 97%
See 1 more Smart Citation
“…Several studies have shown that enhanced chromosomal radiosensitivity is also present in a significant proportion of cancer patients (Scott et al, 1994(Scott et al, , 1998Parshad et al, 1996;Patel et al, 1997;Terzoudi et al, 2000;Baria et al, 2001Baria et al, , 2002Buchholz and Wu, 2001;Papworth et al, 2001;Riches et al, 2001;Baeyens et al, 2002Baeyens et al, , 2005Ban et al, 2004;Howe et al, 2005;Kolusayin Ozar and Orta, 2005;Mozdarani et al, 2005;Distel et al, 2006;Lisowska et al, 2006;Varga et al, 2006). The majority of data have been collected in studies considering breast cancer patients whose lymphocytes were irradiated in the G 2 phase of the cell cycle (Scott et al, 1994Parshad et al, 1996;Patel et al, 1997;Terzoudi et al, 2000;Baria et al, 2001;Buchholz and Wu, 2001;Riches et al, 2001;Baeyens et al, 2002Baeyens et al, , 2005Howe et al, 2005;Djuzenova et al, 2006;Docherty et al, 2007).…”
mentioning
confidence: 99%
“…Pagal šiuos du parametrus yra vertinamas spontaninis pažaidų dažnis, pažaidų po kraujo mėginių in vitro apšvi-tinimo 2 Gy jonizuojančiaja spinduliuote ir pažaidų po radioterapijos seansų dažnis [16,17].…”
Section: Naujas Požiūrisunclassified